2015
DOI: 10.3109/02699052.2015.1004756
|View full text |Cite
|
Sign up to set email alerts
|

How long is too long? The lack of consensus regarding the post-concussion syndrome diagnosis

Abstract: There is a lack of consensus regarding the definition of PCS among physician members of the ACSM. A standard definition would improve consistency in concussion research and in clinical practise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 26 publications
1
53
0
4
Order By: Relevance
“…As mentioned previously, in a study in which more than 500 physicians were surveyed, the majority of the physicians diagnosed PCS in patients with 1 symptom for a minimum of 4 weeks. 42 However, it is important to note that other studies have found an association between concussion symptom inventory scores and PCS. Meehan et al 30 reported that among a host of possible signs and symptoms, only total score on a symptom inventory was associated with symptoms lasting more than 4 weeks.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned previously, in a study in which more than 500 physicians were surveyed, the majority of the physicians diagnosed PCS in patients with 1 symptom for a minimum of 4 weeks. 42 However, it is important to note that other studies have found an association between concussion symptom inventory scores and PCS. Meehan et al 30 reported that among a host of possible signs and symptoms, only total score on a symptom inventory was associated with symptoms lasting more than 4 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…3 In a survey of more than 500 physicians, the majority of them diagnosed PCS in patients who endorsed at least 1 symptom for a minimum of 4 weeks. 42 Many reports have outlined risk factors for PCS, 8,13,15,17,23,25,28,40,45,50,51 but few studies have been performed in an exclusively sports population. 12,26,30,31,33 Documented risk factors for PCS in athletes include initial symptom score, 26,31 loss of consciousness (LOC), 23 amnesia, 26 and female sex, 28,50 although considerable debate has surrounded each factor.…”
mentioning
confidence: 99%
“…104-108 A survey of physician members of the American College of Sports Medicine demonstrated a lack of consensus about how many postconcussion symptoms must be present and how long they must persist to constitute abnormal. 109 The 2012 consensus statement on concussion in sport defines postconcussion symptoms that last beyond 10 days as persistent, 6 whereas the American Medical Society for Sports Medicine requires that symptoms last "weeks to months". 45 Several definitions for the abnormal persistence of postconcussion symptoms have been put forth, with symptom durations ranging from 7 days to 3 months.…”
Section: Clinical Assessment Toolsmentioning
confidence: 99%
“…46 The agreement between DSM-IV and ICD-10 criteria, however, is poor, 46 the DSM-5 has removed the PCS diagnosis entirely in favor of defining mild or major neurocognitive disorder following TBI, 30 and few clinicians even adhere to DSM or ICD guidelines in practice. 47 Large-scale EHR data offer new opportunities to resolve these diagnostic discrepancies by revealing how TBI patients actually cluster and recover clinically. Data-driven approaches have already uncovered novel autism spectrum disorder subgroups using the EHR, 48 and machine learning algorithms applied to EHR data have accurately predicted suicide attempts up to two years in advance.…”
Section: Discussionmentioning
confidence: 99%